2017
DOI: 10.1051/kmae/2017015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of invasiveAcer negundoleaf litter on benthic microbial abundance and activity in the littoral zone of a temperate river in Lithuania

Abstract: -Riparian forests are known as important source of allochthonous organic matter entering to water ecosystems via fallen leaves. However, leaf litter, depending on their quality, may create different conditions for benthic microorganisms functioning in littoral zone of water bodies. In order to evaluate the impact of riparian invasive Acer negundo on littoral water zone of the River Neris (Lithuania), we performed physicochemical and microbiological investigations in bottom sediments of three different sites of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…The LML exhibited a temperature about 1ºC higher than the HML, a value that appears to have been sufficient to accelerate the microbial activity on allochthonous organic matter. A positive effect of the higher temperature on decomposition rates has also been observed in other studies (Krevš & Kučinskiene, 2017;Silva et al, 2018;Song et al, 2013). The results of the present study, however, differ from those of Rezende et al (2018), who observed similarities in the decomposition of allochthonous debris in shallow lakes with different macrophyte coverage in the Brazilian semi-arid region, attributing this similarity to short geographical distance (~300-m) between the study ecosystems, while the lakes in the present study only had a short distance between them (~200 m).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The LML exhibited a temperature about 1ºC higher than the HML, a value that appears to have been sufficient to accelerate the microbial activity on allochthonous organic matter. A positive effect of the higher temperature on decomposition rates has also been observed in other studies (Krevš & Kučinskiene, 2017;Silva et al, 2018;Song et al, 2013). The results of the present study, however, differ from those of Rezende et al (2018), who observed similarities in the decomposition of allochthonous debris in shallow lakes with different macrophyte coverage in the Brazilian semi-arid region, attributing this similarity to short geographical distance (~300-m) between the study ecosystems, while the lakes in the present study only had a short distance between them (~200 m).…”
Section: Discussionsupporting
confidence: 85%
“…Total phosphorus is a limiting factor that can influence the abundance of the main groups in the bacterial community, which favour higher concentrations (Schneider et al, 2012). The results of the present study and those observed in other studies (Krevš & Kučinskiene, 2017;Pascoal & Cássio, 2004) suggest bacteria can make a greater contribution to decomposition in eutrophic systems, especially when fungal activity is restricted.…”
Section: Discussionsupporting
confidence: 68%
“…As to biodiversity, there is certainly a solid argument for the detrimental impacts of NNTs in situations where they reduce richness and diversity of native taxa, or the abundance of native animal or plant populations. A large body of literature has been produced on the impacts of European NNT species on biodiversity, ranging from microbes (Krevš and Kučinskienė 2017) to plant communities (Chabrerie et al 2007), invertebrates (Gossner 2016) or birds (Calviño-Cancela 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The riparian forests in cities are reported to have 10-40% invasive tree species [39,65], and over the last 100 years an increase ash-leaved maple and other IAS in urban floras has been noted [66]. The presence of invasive tree species alters the composition of forests, leading to replacement of the riparian native species [67]. In extreme cases, in the riparian zones the invasion can lead to the development of homogenous communities of novel ecosystems little resembling the former riparian forests [68].…”
Section: Discussionmentioning
confidence: 99%